Spatial Pattern of Road Traffic Accident Casualties in Nigeria - Aderamo, A.J. (Mediterranean Journal of Social Sciences, 2012)
The paper examined the spatial variation of road traffic accident casualties in Nigeria with a view to suggestingmeasures to reduce the scourge. The data used for the study included the total number of deaths and number of injuries fromroad traffic accident in Nigeria for the period 2004 to 2007. These were collected from the Nigerian Police Force Headquartersand the Federal Road Safety Commission. Data were also collected from relevant federal and state ministries. The results of theanalysed data were then shown in map form to depict the spatial variation of road traffic accident casualties across the 36 statesand the Federal Capital Territory. Multiple regression method was then used to model the spatial pattern of road accidentcasualties in Nigeria for the study period. The result showed that spatial variation exists in the incident of road traffic accident inNigeria. The paper finally made recommendations to reduce the carnage on Nigerian roads.